Effect Of Life Skill, Discipline and Motivation Toward Learning Result Pf Sport Subject During Pandemic Covid-19 - Yusup, Maulana; Subarjah, Herman S; sudrazat, Adang (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
Learning outcomes are a measure of the success of students in studying the material that has been delivered within a certain period, learning outcomes are used to determine the position of students against predetermined standards. The application of Life Skills, Discipline, and Motivation is expected to help improve or change students to get better physical education learning outcomes. The population of this study was class VIII students of SMPN 4 Karangpawitan Garut. The population was 98 people, with a sample of 30 students in the experimental group A, experimental group B and 30 students in the experimental control group C. Sampling was carried out using purposive sampling. The research method in this study is Quasi Exsperiment with a pre-test post-test control group design. The improvement of life skills is measured using an instrument from Cronin and Allen (2017), namely the Life Skills Scale for Sport (LSSS) which consists of eight components, namely: teamwork, goal setting, time management, emotional skills, communication, social skills, leadership, and problem solving. solving and decision making. And the increase in discipline and motivation was measured to determine the description of student learning implementation on student learning outcomes at a junior high school in Karangpawitan Garut. Â By using a questionnaire instrument, the results showed that there was a significant increase in life skills, discipline and motivation from each experimental group. The component with the highest improvement is life skills with a teamwork component (teamwork).Â Keywords: Life Skills, Discipline, Motivation, Physical Education.